Seaweeds Secondary Metabolites: Successes in and/or Probable Therapeutic Applications - Pinto, Diana Cláudia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Seaweeds are recognized as highly nutritious, and their use in gastronomy is increasing. Their health benefits and their potential to prevent several diseases have also been established. In this Special Issue several health effects are discussed, with more emphasis on their antitumor activity and potential use to treat Alzheimer's disease. The key bioactive metabolites, from which phlorotannins can be highlighted, are presented, as well as some important in vivo studies. Altogether, the chapters provide in-depth information about the biological activities of seaweed metabolites, contributing to elucidate the health effects of seaweed.